2020
DOI: 10.3389/fvets.2020.589971
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Social Impacts of COVID-19 on Animal Welfare and Dairy Husbandry in Central Punjab, Pakistan

Abstract: Studies on the impact of the COVID-19 pandemic on animal welfare and dairy husbandry in low-income countries are limited. We conducted a survey between February and June 2020 to evaluate the economic impact and animal health problems upon the pandemic. Participants were lead veterinarians from 14 dairy farms with herd size between 100 and 500 in Lahore. These farms were major suppliers of milk and dairy products to central Punjab, Pakistan. During the pandemic, 10 of the 14 dairy farms relied on feed mill conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 25 publications
(29 reference statements)
0
39
0
4
Order By: Relevance
“…A systematic literature review (SLR) at this early stage of literature development, when many research undertakings are being designed or initiated, can identify key research gaps, unresolved questions and avenues for future research in this area. Second, while the effects of COVID-19 on food supply chains in general have prompted growing researchers' attention in the past few months, there is very little evidence on the full direct and indirect impact of the pandemic on livestock supply chains [23] as well as a lack of research based on the experiences of livestock producers and consumers in developing countries [24]. In this respect, Grace et al [25] point out that despite the fact that livestock systems in developing countries have experienced several extreme events in recent years, the ability of the livestock sectors to predict, prevent and control these events is limited and thus there is a need to direct research activities to specific topics of relevance to the context of livestock systems in these countries to implement interventions that enhance their preparedness to future pandemics.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic literature review (SLR) at this early stage of literature development, when many research undertakings are being designed or initiated, can identify key research gaps, unresolved questions and avenues for future research in this area. Second, while the effects of COVID-19 on food supply chains in general have prompted growing researchers' attention in the past few months, there is very little evidence on the full direct and indirect impact of the pandemic on livestock supply chains [23] as well as a lack of research based on the experiences of livestock producers and consumers in developing countries [24]. In this respect, Grace et al [25] point out that despite the fact that livestock systems in developing countries have experienced several extreme events in recent years, the ability of the livestock sectors to predict, prevent and control these events is limited and thus there is a need to direct research activities to specific topics of relevance to the context of livestock systems in these countries to implement interventions that enhance their preparedness to future pandemics.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous major disease outbreaks in recent decades (e.g., SARS, H7N9, Ebola, and Zika), the turbulence caused by COVID-19 mainly affected the downstream stages of the food supply chain [ 14 , 15 ]. That is, COVID-19 has not directly affected the production stages of the poultry supply chain [ 16 ]; however, disruptions in the downstream stages, such as transport and logistics as well as demand and consumption, have knock-back effects on producers [ 17 , 18 ]. For example, the RBN [ 19 ] found that COVID-19 restrictions adversely affected the ability of poultry producers in East African countries to access feed, water resources, and other production inputs and showed that exporters in these countries face significant reductions in demand for livestock-source foods in major importing markets.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a critical look into this emerging literature reveals three major shortcomings. First, the bulk of the literature is focused on developed countries, whereas there is still a lack of research based on the experiences of poultry producers in developing countries [ 18 ]. Second, most of the evidence is extremely aggregated and dominated by continental and regional-level studies and sector-level analyses, e.g., [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the noise level was reduced substantially in most countries because of the imposition of quarantine measures by most governments. The lockdown resulted also in clear water in the canals, clear skies, wild animals roaming streets, and pollution drop, particularly in the industrial areas (Capovilla 2020 ; Corrigan 2020 ; Ficetola and Rubolini 2020 ; Hussain et al 2020 ). The lockdown during COVID-19 caused a great drop in the global consumption of oil and coal, and subsequent decrease in air pollution (IEA 2020 ; Ruiz 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 causes increasing medical waste, inorganic waste as single-use plastic bags, demand for bottled water, plastic packing and packaging, organic waste generated by households, and garbage from personal protective equipment such as masks and gloves (Calma 2020 ; Tenenbaum 2020 ). In addition, environmental pollution is increased due to the tendency of the poor population to use their old cars with cheap petrol that pollute the environment (Hussain et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%